Iron ore development management in the Russian Federation - A. M. Belyaev; F. F. Sharipov; M. A. Dyakonova (Управление)
The Russian mineral resource complex is the basis for economy real sector development. The reserves of oil, gas, ferrous and non-ferrous metals, timber, and other raw materials are the strategic basis for the state economic development stability.   The subject of the study is iron ore, by reserves of which Russia is confidently among the top three countries in the world together with Australia and Brazil.   The global statistics on iron ore production looks a little different since China and India are ahead of Russia in terms of production volumes after the above-mentioned countries. At a time when the country is facing the task of achieving technological sovereignty, and the metallurgical industry is the driver of developing such industries as machine building, construction, and energy, the mineral and raw materials complex development issues are of undeniable interest and relevance.   The technological development strategy of Russia will rely in its implementation on a stable metallurgical industry, where issues and main directions of ferrous metallurgy development have been identified, which are the main purpose of this study.